Synthesis of IGZO ink and study of ink-jet printed IGZO thin films with different Ga concentrations. (December 2017) - Shen, Y.K.; Liu, Z.; Wang, X.L.; Ma, W.K.; Chen, Z.H.; Chen, T.P.; Zhang, H.Y.
Abstract: By dissolving gallium chloride (GaCl3 ), indium chloride (InCl3 ), zinc acetate dihydrate [Zn(OAc)2 ·2H2 O] and monoethanolamine (MEA) into a solvent of 2-methoxyethanol, the IGZO ink was synthesized. Five types of IGZO ink were prepared with different molar ratios of In:Ga:Zn, which can be used for ink-jet printing process. The thermal behaviors of IGZO ink with different formulas were investigated and the ideal annealing temperature for film formation was found to be ∼450 °C. Based on the prepared ink, amorphous IGZO thin films were directly printed on the glass substrate with a FujiFilm Dimatix ink-jet printer, followed by a thermal annealing at 450 °C for 1 h. The surface morphology, crystal structure, optical transmittance, electron mobility and carrier concentration were characterized and investigated. The ink-jet printed amorphous IGZO thin films fabricated in this work can be used as switching medium in flexible resistive random access memory devices.